Uso de isoenzimas para caracterização genética de amostras de Conyza sp. do estado do Paraná - Circunvis, Bruno Cesar (2012)
Increasing studies have been conducted to analyze the genetic diversity of species Conyza bonariensis L., Conyza canadensis L. and Conyza sumatrensis Retz., popularly known as horseweed or motorboat belonging to the Asteraceae family in recent years has caused damage in several crops in Brazil and the world, mainly in soy. Thus, the genetic variability of three populations of Conyza sp. from the northwestern state of Paraná was estimated by isozymes electrophoresis of in starch gel. Were resolved only four isoenzymatic systems (ACP, GPI, MDH and PGM). We detected 10 loci and 10 alleles, which showed no genetic diversity within and among populations analyzed, demonstrated by the presence of only homozygous. Enzymes used in this study indicated that the three populations are genetically uniform for the enzyme systems analyzed.